RNA binding proteins in cancer chemotherapeutic drug resistance - Vembuli, Hemanathan; Gor, Ravi; Ramalingam, Satish; Perales, Selene; Rajasingh, Johnson (Frontiers in Cell and Developmental Biology, 2024)
Drug resistance has been a major obstacle in the quest for a cancer cure. Many chemotherapeutic treatments fail to overcome chemoresistance, resulting in tumor remission.The exact process that leads to drug resistance in many cancers has not been fully explored or understood. However, the discovery of RNA binding proteins (RBPs) has provided insight into various pathways and post-transcriptional gene modifications involved in drug tolerance. RBPs are evolutionarily conserved proteins, and their abnormal gene expression has been associated with cancer progression. Additionally, RBPs are aberrantly expressed in numerous neoplasms.RBPs have also been implicated in maintaining cancer stemness, epithelial-to-mesenchymal transition, and other processes. In this review, we aim to provide an overview of RBP-mediated mechanisms of drug resistance and their implications in cancer malignancy. We discuss in detail the role of major RBPs and their correlation with noncoding RNAs (ncRNAs) that are associated with the inhibition of chemosensitivity. Understanding and exploring the pathways of RBP-mediated chemoresistance will contribute to the development of improved cancer diagnosis and treatment strategies.